Development Of "Green" Energy (Texas Journal of Engineering and Technology, 2024)
Wind farms are one of the key components of the "green" energy system and are gaining significant recognition as a sustainable and environmentally friendly solution to our ever-growing energy needs. This article provides information on the main features, advantages and future prospects of wind and solar power plants. Using information about green energy has been shown to increase the content and effectiveness of higher education. The understanding that the transition to renewable energy sources, "Green" energy is the need of the hour has been strengthened.